The biology of Mustelus schmitti in southern Patagonia, Argentina - Chiaramonte, Gustavo Enrique (2000)
The relationship of body weight and total length (L(T)) of Mustelus schmitti in southern Patagonia was different between sexes. Changes in maturity stages in males appear at larger sizes in Ria Deseado specimens than in the Mar del Plata area. Mature females ranged from 795 to 913 mm while all male specimens >759 mm L(T) were mature. The data suggest that mating occurs before parturition, with simultaneous ovulation. The diet of adult M. schmitti was mainly carcinophage and the diet of young-of-the-year and adults differed. The young-of-the-year use the Ria Deseado as a pupping area.